2006
DOI: 10.1590/s1020-49892006000100014
|View full text |Cite
|
Sign up to set email alerts
|

Comissões farmacoterapêuticas no Brasil: aquém das diretrizes internacionais

Abstract: The inadequate use of drugs leads to lack of therapeutic efficacy, adverse reactions, side effects, preventable drug interactions, increased bacterial resistance to antibiotics, and wasted resources. Changing this scenario is one of the most complex challenges facing health systems today. One approach used to rationalize the use of drugs lies in the creation of pharmacy and therapeutics committees, whose main role is to guide and assist health institutions at all levels in selecting drugs and monitoring their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
1
24

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 12 publications
1
9
1
24
Order By: Relevance
“…Our study has shown that only 36 (14.2%) of the new medicines registered during these 13 years were listed for public coverage under the SUS, and that 21 out of the 36 medicines included in these listings were considered non-innovative by both CMED and Prescrire. Such a low number of therapeutic innovations stresses the importance of strengthening pharmacy and therapeutics committees 39,40,41 . While they have been established in many health facilities in Brazil, their roles are somewhat limited due to financial and human resources constraints 41 .…”
Section: Percentage Within Atc Class (%)mentioning
confidence: 99%
“…Our study has shown that only 36 (14.2%) of the new medicines registered during these 13 years were listed for public coverage under the SUS, and that 21 out of the 36 medicines included in these listings were considered non-innovative by both CMED and Prescrire. Such a low number of therapeutic innovations stresses the importance of strengthening pharmacy and therapeutics committees 39,40,41 . While they have been established in many health facilities in Brazil, their roles are somewhat limited due to financial and human resources constraints 41 .…”
Section: Percentage Within Atc Class (%)mentioning
confidence: 99%
“…Estas funções são de extrema importância para a melhoria da gestão, mas no caso do estudo ainda não ocorre de fato. 2,5 Visando buscar ferramentas que minimizem e eliminem as discrepâncias entre as indicações do protocolo e a dispensação do medicamento, as seguintes propostas foram elaboradas:…”
Section: Propostas De Melhorias Para Os Processos De Trabalhounclassified
“…Estudos mostram que em países desenvolvidos como Canadá e Estados Unidos as CFTs possuem papel fundamental nas variáveis econômicas, sociais, sanitári-as para avaliar a incorporação de medicamentos a padronização das unidades hospitalares. 2,5 No Brasil, a atuação das CFTs é incipiente e existem poucos estudos sobre a sua existência e a metodologia de trabalho utilizada. 1,5 Portanto, o presente estudo pretende apresentar a CFT do HCFMRP-USP quanto a sua funcionalidade e desenvolver uma análise crítica do seu atual funcionamento.…”
unclassified
See 1 more Smart Citation
“…DTC activities are well established in most European countries, the USA, Canada and Australia. In Brazil, these committees are non-mandatory, and their implementation has not been forthcoming (Marques, Zucchi, 2006;Veber et al, 2011). A 2003 national assessment showed that a mere 29 (11%) of 250 investigated hospitals presented nominal DTCs, but operational DTCs were seen in only 3.6% of hospitals (Osorio-de-Castro, Castilho, 2004).…”
Section: Introductionmentioning
confidence: 99%